The Influence of Trust and Perceived Usefulness on Purchase Intention with Price Mediation - Fratama, Feri; Pardede, Ratlan; Samara, Aldi; Susanti, Metta (PT Inovasi Pratama Internasional, 2023)
This research aims to determine the influence of trust and perceived usefulness on purchase intention which is mediated by price (empirical study: Shopee Indonesia users in Tangerang). Research data was obtained from distributing questionnaires via Google Forms. Samples were taken using purposive sampling technique. The sample used in this research was 256 respondents. This research uses quantitative analysis techniques and is processed using AMOS. The research results show that Trust and Perceived Usefulness have a positive and significant effect on price. This research can provide benefits in the form of knowledge to academics, practitioners and stakeholders. Besides that, this research can provide ideas for designing and developing marketing plans and sales strategies where Shopee companies can improve the welfare of the community through the benefits obtained through value by using Shopee.